Microwave activation of electrochemical processes: High temperature phenol and triclosan electro-oxidation at carbon and diamond electrodes - Ghanem, M; Compton, R; Coles, B; Psillakis, E; Kulandainathan, M; Marken, F (Elesvier, 2007)
The electrochemical oxidation of phenolic compounds in aqueous media is known to be affected by the formation of electro-polymerized organic layers which lead to partial or complete electrode blocking. In this study the effect of high intensity microwave radiation applied locally at the electrode surface is investigated for the oxidation of phenol and triclosan in alkaline solution at a 500 μm diameter glassy carbon or at a 500 μm × 500 μm boron-doped diamond electrode. The temperature at the electrode surface and mass transport enhancement are determined by calibration with the Fe(CN)63-/4- redox system in aqueous 0.3 M NaOH and 0.2 NaCl (pH 12) solution. The calibration shows that strong thermal and mass transport effects occur at both glassy carbon and boron-doped diamond electrodes. The average electrode temperature reaches up to 390 K and mass transport enhancements of more than 20-fold are possible. For the phenol electro-oxidation at glassy carbon electrodes and at a concentration below 2 mM a multi-electron oxidation (ca. 4 electrons) occurs in the presence of microwave radiation. For the electro-oxidation of the more hydrophobic triclosan only the one-electron oxidation occurs. Although currents are enhanced in presence of microwave radiation, rapid blocking of the electrode surface in particular at high phenol concentrations still occurs.